2018
DOI: 10.1111/jop.12703
|View full text |Cite
|
Sign up to set email alerts
|

Haematinic deficiencies and patient clinical profiles in Polish patients with recurrent aphthous stomatitis (RAS)

Abstract: The results of our study indicate an association between iron and vitamin B12 deficiency and RAS in a Polish population. However, as the haematinic deficiencies did not significantly modify the course and clinical phenotype of the disease, further studies to explore their role in RAS aetiology are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Some studies have suggested a significant relationship of RAU with the overall deficiency of vitamins and minerals [15,17,31,[33][34][35]; however, these differences dilute when each vitamin or mineral is separately studied [9,36]. Our results could not confirm the association of ulcers and vitamin B 12 deficiency, perhaps because the statistical analysis was performed considering the sole deficiency of this vitamin, or because several factors related to RAU could have been present simultaneously in our patients.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Some studies have suggested a significant relationship of RAU with the overall deficiency of vitamins and minerals [15,17,31,[33][34][35]; however, these differences dilute when each vitamin or mineral is separately studied [9,36]. Our results could not confirm the association of ulcers and vitamin B 12 deficiency, perhaps because the statistical analysis was performed considering the sole deficiency of this vitamin, or because several factors related to RAU could have been present simultaneously in our patients.…”
Section: Discussionmentioning
confidence: 60%
“…Our results could not confirm the association of ulcers and vitamin B 12 deficiency, perhaps because the statistical analysis was performed considering the sole deficiency of this vitamin, or because several factors related to RAU could have been present simultaneously in our patients. On the other hand, it may be possible that the importance of the association of nutritional deficiencies to RAU may be less than previously attributed to their etiopathogenesis, or that all the related factors may only be considered as precipitants for the development of aphthae, as suggested by other authors [9,17,37]. Some other causes such as vigorous tooth-brushing, the use of a hard tooth brush, anesthesia infiltration, or dental treatment may frequently trigger the development of RAU [38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is seen in otherwise healthy people, but also in various infectious and non-infectious diseases, including celiac disease (CD) [1,[6][7][8][9][10][11][12][13][14][15]. In addition, RAS is associated with genetic predisposition, iron and vitamin B12 deficiency, local mechanical injuries, stress, and hormonal imbalance [16,17,18]. We present an obese adolescent with RAS as the only clinical manifestation that indicated a CD.…”
Section: Introductionmentioning
confidence: 99%
“…deficiencies, especially in iron, group B vitamins, vitamin C, folate, or zinc may contribute to RAS 18. If necessary, replacement therapies should be done.…”
mentioning
confidence: 99%